ANALISIS PERHITUNGAN PPH 21 ATAS PENGHASILAN DOKTER SPESIALIS DI RUMAH SAKIT MUHAMMADIYAH KALITIDU, BOJONEGORO - Nurul Mazidah; Dina Alafi Hidayatin; Susy Annisa (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2020)
This study aims to analyze the calculation of PPh 21 on the income of specialist doctors conducted by Muhammadiyah Hospital Kalitidu Bojonegoro, whether it is in accordance with the applicable tax regulations. The study was conducted on six specialist doctors who have the income of more than one employer. The method used is descriptive qualitative. This analysis was conducted by comparing the calculation according to the method adopted earlier by Muhammadiyah Hospital Kalitidu Bojonegoro with the method in accordance with The Regulation of the Director General of Tax No. PER-16/PJ/2016. The results showed that the calculation of PPh 21 specialist doctors who had been carried out by Muhammadiyah Kalitidu Bojonegoro Hospital was not in accordance with the applicable regulations in Indonesia, so the hospital was required to make adjustments to the approximately / more paid PPh 21 that had been collected.